Dietary Intake and Adherence to the Recommendations for Healthy Eating in Patients With Type 1 Diabetes: A Narrative Review - Pancheva, Rouzha; Zhelyazkova, Desislava; Ahmed, Fatme; Gillon-Keren, Michal; Usheva, Nataliya; Bocheva, Yana; Boyadzhieva, Mila; Valchev, Georgi; Yotov, Yoto; Iotova, Violeta (Frontiers in Nutrition, 2021)
Background: Medical nutrition therapy is essential for all people with diabetes, of any type or severity. Compliance with the recommended nutrition is an integral part of the treatment of type 1 diabetes (T1D). It remains unclear to what extent the dietary intake of patients with type 1 diabetes adheres to the recommendations for healthy eating. Objective: The primary aim of our study is to collect and analyze published articles on the nutrition of T1D patients in comparison with the general population and recommendations. Research Strategy and Methods: A literature search for articles, published between January 2006 and July 2021 was conducted, using electronic databases (PubMed and Google Scholar) for all available publications in English and Bulgarian. The process of study selection, identification, screening, eligibility and inclusion followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) recommendations for a flowchart (Figure 1). Based on the keywords search, 425 titles were retrieved, of which 27 were selected based on title and abstract. All papers were crosschecked and reviewed for selection by 3 independent reviewers. As a result, 19 titles were eligible and met inclusion criteria for a full review. Results: Energy intake tends to be lower in T1D patients or comparable to controls and in most cases within the general recommendations. The percentage of calories from protein is within the recommendations for children, adolescents and adults. Only two studies showed that T1D patients consume significantly less than the recommendation for total fat intake (<35E%). The median intake of carbohydrates is in the lower end of the recommended 45 to 60 E%. The median intake of dietary fibre adjusted for total energy is too low for T1D patients and the general population. Conclusion: Study findings suggested a lack of knowledge or misunderstanding of diabetes dietary management. Patients with T1D, who are being consulted with a dietician as a part of their treatment plan may have better compliance to their recommended diet and as a result, are likely to have better health outcomes. Nutritional therapy should focus not only on pure carbohydrate counting but also on healthy eating and complication prevention.